2018
DOI: 10.4236/ojog.2018.814150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Use of Jadelle Contraceptive Implant by Women in the City of Parakou in 2016

Abstract: Introduction: Maternal mortality is still very high in Benin. Being one of the methods of reducing this mortality, contraception is still very rarely used in Benin, particularly in Borgou district. The objective of this work was to evaluate the experience of using Jadelle contraceptive implants by women in the city of Parakou in the Borgou department. Methodology: This was a descriptive cross-sectional study, with retrospective and prospective data collection over the period from March 1 to July 31, 2016. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Similar findings with different percentages were also observed in other studies. 4,19,20 In this study, 78% of participants discussed with their husbands about taking implants as observed in other studies. 3,4,18 Birth spacing was the main reason for using implants among 66.5% of participants in this study.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Similar findings with different percentages were also observed in other studies. 4,19,20 In this study, 78% of participants discussed with their husbands about taking implants as observed in other studies. 3,4,18 Birth spacing was the main reason for using implants among 66.5% of participants in this study.…”
Section: Discussionsupporting
confidence: 68%
“…This result is similar to those of other studies. 9,10,17,19,21 There are some other negative reasons for discontinuation like menstrual disturbances (18.38%), pain or discomfort (16.17%), increased bleeding (11.02%), etc. Some other studies revealed some reasons for discontinuation such as discontent with the bleeding pattern, switching to another method, pain or discomfort, inconvenience to use, husband disapproval, etc with different percentage values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation